Penerapan Distraksi Audio Visual pada Prasekolah Menggunakan Smart Book terhadap Penurunan Skala Nyeri Setelah Pemasangan Infus - Tresia Veny; Ketut Suryani; Vincencius Surani (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
The IV infusion process will cause pain that can be disturbing for children. Pain is a form of uncomfortable sensation that is felt personally by each individual. In addition, there will be changes in vital signs such as increased pulse, blood pressure, and respiration so that it will be an unpleasant experience for children. Non-pharmacological therapy as an intervention to reduce pain perception in children and increase comfort during medical procedures. One form of non-pharmacological technique is audio visual distraction using a smart book. Smart books are fun and interactive play therapy that can support cognitive, fine motor, and sensory aspects in children and to divert children's attention from pain by displaying more pleasant and interesting images and musical sounds so that it can reduce the pain scale after IV installation. The design used in the preparation of this Final Scientific Paper for Nurses is a case study with an intervention in the form of audio visual distraction using a smart book for ± 10 minutes. The number of respondents was 3 people, the intervention was carried out on September 14, October 7, and November 24, 2025, located in the Theresia Charitas Hospital Palembang room. After the smart book audio visual distraction therapy, there was a decrease in the pain scale for 3 respondents, namely in An. A from a pain scale of 7 to a pain scale of 4, An. G from a pain scale of 10 to a pain scale of 4, and An. R from a pain scale of 7 to a pain scale of 4. The application of EBP smart book audio visual distraction therapy can be used to reduce the pain scale in preschoolers after IV installation.